Googling the City: In Search of the Public Interest on Toronto’s ‘Smart’ Waterfront - Morgan, Kevin (2020)
Toronto’s Quayside waterfront regeneration project has become an international reference point for the burgeoning debate about the scope and limits of the digitally enabled ‘smart city’ narrative. The project signals the entry of a Google affiliate into the realm of ‘smart urbanism’ in the most dramatic fashion imaginable, by allowing them to potentially realise their long-running dream for “someone to give us a city and put us in charge.” This article aims to understand this on-going ‘smart city’ experiment through an exploration of the ways in which ‘techno-centric’ narratives and proposed ‘disruptive’ urban innovations are being contested by the city’s civic society. To do this, the article traces the origins and evolution of the partnership between Waterfront Toronto and Sidewalk Labs and identifies the key issues that have exercised local critics of the plan, including the public/private balance of power, governance, and the planning process. Despite more citizen-centric efforts, there remains a need for appropriate advocates to protect and promote the wider public interest to moderate the tensions that exist between techno-centric and citizen-centric dimensions of smart cities.